Pancasila in the Metaverse Era: Opportunities and Challenges in Shaping National Identity - Bambang Yuniarto (CV Tirta Pustaka Press, 2025)
Metaverse technology has created a new virtual space that influences individuals in shaping their identities, engaging in social interactions, and expressing cultural values within a digital context. This phenomenon presents serious challenges to the continuity of national identity, especially amid the rapid currents of globalization. This study aims to examine strategies for integrating Pancasila values into the Metaverse ecosystem to strengthen Indonesia’s national identity. Employing a systematic literature review approach, the study analyzes several relevant scholarly articles to identify trends, characteristics, and thematic syntheses related to Pancasila and the formation of national identity in digital spaces. The findings indicate that Pancasila values such as mutual cooperation (gotong royong), social justice, and tolerance hold significant potential to be internalized within the Metaverse through character education approaches based on immersive technology. However, the application of these values requires a contextual pedagogical design and strong ideological awareness to prevent them from being reduced to mere digital simulations. This research contributes theoretically to the development of a conceptual model linking value education, digital technology, and national ideology. It also offers practical recommendations for educators and policymakers to design learning strategies aligned with national values in this era of technological disruption. Furthermore, these findings open avenues for further exploration of the role of ideology in increasingly dominant virtual spaces.